PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT ROBERE MANAJEMEN INDONESIA JAKARTA - Marcell Pratama`; ARMAN SYAH; AHMAD NAZIR (Yayasan Sahabat Cendekia Jaya, 2024)
Purpose Purpose of this study is to analyze the influence of training programs and the level of work discipline on employee performance at PT Robere Management Indonesia. Methods The research methodology uses a quantitative method with the entire population of employees at PT Robere Management Indonesia. The sample consists of 59 respondents selected using saturated sampling techniques. Data analysis was conducted using simple linear regression tests, multiple linear regressions, correlation coefficients, determination coefficients, partial t-tests, and simultaneous F-tests. Findings The research results show that There is a positive and significant influence between Job Training (X1) and Performance (Y) at PT Robere Management Indonesia. There is a positive and significant influence between work discipline (X2) and Performance (Y) at PT Robere Management Indonesia. The research results show that Simultaneously, there is a positive and significant influence between Job Training (X1) and Work Discipline (X2) on Performance (Y) at PT. Robere Management Indonesia. Implications The implications of this study underscore the importance of training programs and increasing the level of work discipline in improving employee performance in the management consulting company.